Chagas Disease Cardiomyopathy: Immunopathology and Genetics. (19th August 2014) - Cunha-Neto, Edecio; Chevillard, Christophe
Abstract : Chagas disease, caused by the protozoan Trypanosoma cruzi, is endemic in Latin America and affects ca. 10 million people worldwide. About 30% of Chagas disease patients develop chronic Chagas disease cardiomyopathy (CCC), a particularly lethal inflammatory cardiomyopathy that occurs decades after the initial infection, while most patients remain asymptomatic. Mortality rate is higher than that of noninflammatory cardiomyopathy. CCC heart lesions present a Th1 T-cell-rich myocarditis, with cardiomyocyte hypertrophy and prominent fibrosis. Data suggest that the myocarditis plays a major pathogenetic role in disease progression. Major unmet goals include the thorough understanding of disease pathogenesis and therapeutic targets and identification of prognostic genetic factors. Chagas disease thus remains a neglected disease, with no vaccines or antiparasitic drugs proven efficient in chronically infected adults, when most patients are diagnosed. Both familial aggregation of CCC cases and the fact that only 30% of infected patients develop CCC suggest there might be a genetic component to disease susceptibility. Moreover, previous case-control studies have identified some genes associated to human susceptibility to CCC. In this paper, we will review the immunopathogenesis and genetics of Chagas disease, highlighting studies that shed light on the differential progression of Chagas disease patients to CCC.